Monetary theory and policy experience : papers of the IEA conference held in Trento, Italy - Leijonhufvud, Axel (Edt)/ International Economic Association (Cor); Leijonhufvud, Axel.; International Economic Association (New York : Palgrave, 2001)
Why do governments prefer to limit themselves to a specific inflation target? Specialists and senior officials of the European Central bank, the OECD and national central banks look beyond inflation targeting as the goal of monetary policy. Among the contributing, Nobel Laureate Robert Mundell surveys the history and prospects of the sovereignty of the state over money, while Michael Bordo and Lars Jonung use data of 14 industrialized countries to show relationships between fiscal and monetary regimes.
Papers of the conference held on Sept. 4-7, 1997 at the University of Trento.
"In association with International Economic Association."
Includes bibliographical references and index.
rpm 08/05/13
Loans
rpm 08/05/13
Keywords: Monetary policy -- Congreses; Inflation (Finance); Banks and banking, Central